Measuring smallholder dairy farmers’ social valuation of climate mitigation: A case study from Kenya - Florez, Jesus Fernando; Gonzalez Quintero, Ricardo; Pazos Cardenas, Mateo; Triana Ángel, Natalia; Enciso, Valentina; Waluse, Kenneth; Notenbaert, An; Burkart, Stefan (Frontiers, 2025)
Livestock systems in Sub-Saharan Africa contribute substantially to greenhouse gas emissions and are highly vulnerable to climate change. In Kenya, smallholder dairy farmers need to balance productivity with environmental sustainability while facing increasing climate pressures. This case study examines farmers’ perceptions and social valuation of forage-based climate mitigation strategies, focusing on awareness, perceived value, and willingness to adopt improved forages for resilience. The study was conducted in Nandi and Uasin Gishu counties with 46 dairy farmers purposively selected from ongoing project-supported initiatives. A socio-ecological systems perspective informed the analysis. A composite social value indicator integrating knowledge, perception, and use dimensions was constructed using principal component analysis. Findings show high climate awareness and recognition of the benefits of forage-based mitigation. However, willingness to adopt these practices remains limited due to financial, technical, and institutional constraints. Support for improved forages is nonetheless strong, driven by perceived gains in productivity and environmental sustainability. While differences related to gender and age were observed, these were not explored in depth, as the study prioritizes methodological application rather than demographic analysis. Results reveal a persistent gap between awareness and action, indicating that social acceptance alone does not ensure adoption. Strengthening adoption will require improved access to forage seeds, inclusive extension services, capacity building, and targeted climate finance. The study demonstrates the utility of social valuation approaches to assess mitigation readiness and inform socially grounded climate strategies in smallholder dairy systems.